Single crystal growth and characterization of (TlBiSe2)1_ x-(TlBiS2)x narrow gap mixed crystals - Özer, Mehmet; Paraskevopoulos, K. M.; Anagnostopoulos, A. N.; Kokkou, S.; Polychroniadis, E. K. (My University, 1998)
Large single crystals of the family of layered compounds - were grown by the Bridgman-Stockbarger method for x = 0.0, 0.25, 0.50, 0.75 and 1.0. The structures of the as-grown single crystals were determined by x-ray diffraction and the lattice parameters and unit cell volumes were obtained. Infrared reflectivity measurements were also performed in the range 600-. From the analysis, the parameters , and were calculated. The electrical resistivities and (parallel and perpendicular to the layers, respectively) were measured as a function of temperature. From the measurements the plot of the Debye temperature versus x was calculated. An attempt was also made to correlate these physical properties with the compositional parameter x.